Undergraduate research in medical education: a descriptive study of students' views - Oliveira, Cristiano C. [UNESP]; Souza, Renata C. de [UNESP]; Sassaki Abe, Erika H. [UNESP]; Silva Moz, Luis E. [UNESP]; Carvalho, Lidia R. de [UNESP]; Domingues, Maria Aparecida Custódio [UNESP] (Biomed Central Ltd., 2014)
Background: Medical students engage in curricular and extracurricular activities, including undergraduate research (UR). The advantages, difficulties and motivations for medical students pursuing research activities during their studies have rarely been addressed. In Brazil, some medical schools have included undergraduate research into their curriculum. The present study aimed to understand the reality of scientific practice among medical students at a well-established Brazilian medical school, analyzing this context from the students' viewpoint.Methods: A cross-sectional survey based on a questionnaire applied to students from years one to six enrolled in an established Brazilian medical school that currently has no curricular UR program.Results: The questionnaire was answered by 415 students, 47.2% of whom were involved in research activities, with greater participation in UR in the second half of the course. Independent of student involvement in research activities, time constraints were cited as the main obstacle to participation. Among students not involved in UR, 91.1% said they favored its inclusion in the curriculum, since this would facilitate the development of such activity. This approach could signify an approximation between the axes of teaching and research. Among students who had completed at least one UR project, 87.7% said they would recommend the activity to students entering the course.Conclusion: Even without an undergraduate research program, students of this medical school report strong involvement in research activities, but discussion of the difficulties inherent in its practice is important to future developments.